Tectonic stress regime and faulting style analysis due to sequence of earthquakes in Western Nepal - Pooja Mahto; S.C. Gupta (Natural Hazards Research)
The current study examines the source mechanism and the regional stress regime of a sequence of moderate-sized earthquakes between October 2022 and October 2023. ISOLA-GUI-a Matlab coded program has been used to estimate Moment Tensor Solution to understand the source mechanisms of the earthquakes in the region. The earthquakes are recorded at the broadband station arrays of the regional seismological network around the Tehri region, installed by the Indian Institute of Technology Roorkee in India. The study focuses on earthquakes with epicentral distances of less than 10°. The investigation aims to comprehend the source process by estimating the focal mechanisms utilizing regional waveform data and then inverting the acquired focal mechanism of these earthquakes to comprehend the active stress regime in the region. The obtained source mechanism reveals a predominance of a double-couple mechanism in faulting and hence, suggests that the majority of the seismic energy is released through shear motion along a defined fault plane. By revealing the complex interaction of geological forces in the Himalayan belt, this investigation will help us to better understand the distribution of stress and deformation patterns beneath the Earth's crust. The main emphasis lies on assessing stress distribution through the utilization of earthquake focal mechanism data and employing the Stress Inversion technique using the WinTensor program. The result of stress inversion suggests that the maximum compressive stress is plunging horizontally, while the minimum compressive stress is oriented vertically. Hence revealing a thrust stress regime in Western Nepal, trending in the NNE- SSW direction corroborating the ongoing tectonic processes associated with the collision of the Indian plate with the Eurasian plate.